THE STRATEGIC ROLE OF SUSTAINABILITY REPORTING IN ACHIEVING NET ZERO EMISSIONS PLATES - Mohamad Djasuli; Ani Fitriya; Rifkotul Mu’minah; Fara Dilla; Aulia Parsa Nadhiraah (Universitas Muhammadiyah Tangerang, 2026)
The escalating climate crisis necessitates corporate commitment to achieving Net Zero Emissions (NZE). This study investigates the strategic contribution of Sustainability Reporting (SR) to NZE through a systematic literature review of 37 peer-reviewed articles (2020-2025). Analysis reveals SR fulfills three strategic functions: legitimacy enhancement (89.2% of studies), transparency improvement (75.7%), and green innovation facilitation (67.6%). Significant implementation obstacles include standard inconsistency (64.9%) and greenwashing vulnerability (59%). Digital technology integration (AI, blockchain) is a promising solution (43.2%). Findings urge regulatory strengthening (78.4%) and digital adoption. For Indonesia, where only 42% of large firms report consistently, mandatory SR and a national ESG assurance institute are critical to accelerate a credible low-carbon transition